Kewarganegaraan dan Hak Politik : Analisis Undang-Undang tentang Hak Pilih Warga Negara di Indonesia - Ahmad Muhamad Mustain Nasoha; Ashfiya Nur Atqiya; Lutfi Lailatul Hikmah; Muhammad Fahrurrozi; Muhammad Muhyihuddin Abdul Qodir Jailli (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Citizenship is a legal status that gives a person rights and responsibilities as a citizen. Many laws in Indonesia regulate political rights, including the right to vote. One of them is Law Number 7 of 2017 concerning General Elections. Within Indonesia's democratic framework, the right to vote is an important expression of popular sovereignty, allowing voters to actively elect their leaders at both the legislative and executive levels. Fulfilling the right to vote cannot be separated from various technological, political and social difficulties that may have an impact on democracy in Indonesia. Over the last five years, several dynamics have emerged in the enforcement of voting rights regulations, including changes to regulations, election implementation, and the application of digital technology to increase election transparency and accountability. Despite the implementation of legal and technological reforms, there are still challenges in verifying permanent voter lists, especially for vulnerable groups such as people with disabilities and those living in remote locations or abroad, which continues to hinder efforts to tackle disinformation and hoaxes on social media. This research examines the political rights of Indonesian individuals, especially regarding their right to vote in general elections as regulated by law. The right to vote is one manifestation of political participation that is recognized internationally and guaranteed in various national legal instruments.